THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN CULTIVATING STUDENTS' HABITS OF PERFORMING CONGREGATIONAL PRAYERS - Sofian, Mohammad Nur (ASWAJA: Jurnal Pendidikan dan Keislaman, 2024)
The purpose of this thesis is to obtain objective data on the role of Islamic Religious Education (PAI) teachers in fostering the habit of congregational prayer at Madrasah Aliyah Al-Khairiyah Jakarta. The focus of the research includes: (1) the implementation of Islamic religious education, (2) the implementation of congregational prayer for students, and (3) the role of PAI teachers in fostering the habit of congregational prayer at the madrasah. The method used is inductive qualitative research with data collection techniques through observation, interviews, documentation, and questionnaires. The results of the study indicate that the implementation of Islamic religious education has been running well according to the curriculum. However, the implementation of congregational prayer for students is still ineffective because participation in the prayer room is still low. The role of PAI teachers in fostering the habit of congregational prayer is also considered less than optimal. The implications of the research emphasize the importance of increasing teacher responsibility in accompanying students, providing examples in implementing congregational prayer, and providing educational sanctions for students who do not implement it.